Stability of selected PAHs in sewage sludge = Stabilność wybranych WWA w osadach ściekowych - Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the investigations was to estimate the half-life of selected PAHs in sewage sludge. Five hydrocarbons selected from 16 PAHs- EPA were chosen. In this study, the quantity changes in the concentration 3- and 4-ring of PAHs in sewage sludges were investigated.
Keywords: fluoren; fenantren; antracen; fluoranten; piren; czas półrozpadu; osady ściekowe; warunki tlenowe; azydek sodu; fluorene; phenanthrene; anthracene; fluoranthene; pyrene; half-live; sewage sludge; aerobic conditions; sodium azide